2021
DOI: 10.1016/j.ajem.2020.08.068
|View full text |Cite
|
Sign up to set email alerts
|

A coronavirus disease 2019 (COVID-19) patient with bilateral orchitis

Abstract: During the development of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2), a myriad of complications has emerged and although rare, several genitourinary complications have been reported. The bulk of these complications have been secondary to hypercoagulable states, such as priapism. Previous SARS family infections have caused orchitis, though no adult cases of orchitis have been reported. We describe a novel case of SARS-CoV2 bilateral orchitis in a previously healthy 37-year-old male who pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 9 publications
0
43
0
2
Order By: Relevance
“…Low flow priapism was reported in 2 patients 23,30 . Scrotal ultrasound was performed in 4 studies 20–22,24 : acute orchitis was found in 10 patients, acute epididymitis in 7, and acute epididymo‐orchitis in 16 20, 22, 24 ; one case of bilateral nonspecific intratesticular increased blood flow was also described 21 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low flow priapism was reported in 2 patients 23,30 . Scrotal ultrasound was performed in 4 studies 20–22,24 : acute orchitis was found in 10 patients, acute epididymitis in 7, and acute epididymo‐orchitis in 16 20, 22, 24 ; one case of bilateral nonspecific intratesticular increased blood flow was also described 21 …”
Section: Resultsmentioning
confidence: 99%
“…Further assessment of eligibility, based on full-text papers, led to the exclusion of nine papers. Finally, 16 studies involving a total of 575 patients infected with SARS-CoV-2 who had been evaluated for urinary and/or male genital involvement between January and June 2020 were included in the final analysis [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] (Figure 1). The characteristics of selected studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Another reported orchiepididymitis case was in a 43‐year‐old COVID‐19 diabetic patient who complained about testicular pain and had bilateral inhomogeneous enlargement of the testis and the epididymis, and soft augmentation of colour Doppler blood flow (La Marca et al., 2020). In another report, a young adult with COVID‐19 developed bilateral orchitis but without sonographic epididymal changes (Bridwell et al., 2020). A single‐centre‐based Chinese study reported orchiepididymitis in symptomatic and nonsymptomatic patients regarding scrotum symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…2020). A Turkish prospective study reported 10.98% of testicular pain in hospitalised COVID‐19 patients (Ediz et al., 2020); however, very few acute orchitis and orchiepididymitis anecdotal cases caused by confirmed SARS‐CoV‐2 infection were reported in adolescent and adult patients (Bridwell et al., 2020; Gagliardi et al., 2020; La Marca et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic was initially accompanied with an explosion of case reports. Flicking through Twitter on the commute, one learnt that 'COVID-19 causes pancreatitis 1 ', 'COVID-19 causes encephalitis 2 ' and 'COVID-19 causes orchitis 3 ' which left you wondering what inflammatory condition the disease was not associated with. It soon became apparent that gastrointestinal symptoms were not uncommon and that they may be associated with a more severe disease phenotype.…”
mentioning
confidence: 99%